Designing Administrative Reforms for Maintaining Trust. Issue 3 (17th February 2021) - Klemsdal, Lars; Kjekshus, Lars Erik
ABSTRACT: This paper explores how to maintain trust while implementing administrative reforms. The contribution is to show how trust can be enhanced through the design of reform plans. Contrary to the position that favours trust-based management over authority-based management, this paper favours a relational understanding of managing trust, which involves balancing authority and openness towards employees' involvement. Moreover, different situations will require different balance points between the two dimensions. The notion of 'minimal critical specification design' is advanced as a sensitizing conceptualisation of optimal reform designs for maintaining trust during implementation. The argument is illustrated through the case of a large administrative reform within the Norwegian welfare sector.